The Paulicians heresy, persecution, and warfare on the Byzantine frontier, c.750-880 - Dixon, Carl (Leiden Boston Brill, 2022)
"Disavowing their traditional portrayal as the progenitors of medieval Christian dualism, this book recasts the Paulicians as broadly conventional Christians inspired by the apostle Paul. Using previously neglected Paulician testimony and a critical reappraisal of the existing sources, it explains their fleeting regional prominence via a pluralistic approach to Paulician identity within the complex socio-religious milieus of Armenia and Asia Minor. Exploring their history of schism, persecution, and resistance, it reassesses their relationship with the iconoclast controversy and the changing fortunes of Byzantine-Islamic warfare, shedding new light on their obscure but fascinating transformation from itinerant preachers to militarized insurrectionists"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Paulicians; Church History -- Middle Ages, 600-1500; Byzantine Empire -- Church history